Effect of a Preemptive Femoral Nerve Block on Cytokine Release and Hyperalgesia in Experimentally Inflamed Skin of Human Volunteers. Issue 6 (1st October 2010) - Horstman, Damian J.; Carvalho, Brendan; Aleshi, Pedram; Angst, Martin S.
Abstract : Background and Objectives: Tissue injury is associated with the local release of inflammatory and nociceptive mediators and the development of hyperalgesia. It is unclear whether interrupting neuronal signaling using regional anesthetic techniques at the time of the injury modifies local nociceptive and inflammatory processes. The aim of this study was to determine whether a peripheral nerve block at the time of tissue injury could modify the development of wound hyperalgesia and the local release of inflammatory and nociceptive mediators. Methods: Twelve healthy volunteers participated in this controlled, crossover, randomized study. A femoral nerve block or a sham block was established before inducing an experimental UVB burn on the thigh. Twenty-four hours later, the interstitial wound fluid was sampled, and mechanical and heat pain thresholds were assessed. Wound fluid concentrations of an array of cytokines, chemokines, nerve growth factor, prostaglandin E2, and substance P were determined. Results: Skin inflammation was associated with the release of inflammatory and nociceptive mediators and resulted in significant tissue hyperalgesia ( P < 0.001). However, the presence of a fully established peripheral nerve block at the time of tissue injury did not alter the development of hyperalgesia after regression of the block. Similarly, the presence of a peripheral nerve block did not modify the release of inflammatory or nociceptive mediators. Conclusions: These findings suggest that a preemptive, single-shot peripheral nerve block minimally affects wound hyperalgesia and inflammation. Continuous nerve block techniques may be better suited to alter nociceptive and inflammatory events in wounds beyond the duration of the block.